Homelessness in the Urban Landscape: Beyond Negative Aesthetics. (2nd January 2018) - Untea, Ionut
Abstract: The great popularity of homelessness as an artistic theme in the twentieth century and beyond may be explained by the frequency by which the everyday image of homeless persons impacts upon the passerby's aesthetic perception of the urban environment. Nonetheless, as yet, homelessness has not been included in the field of the aesthetics of everyday life. This article is meant to fill this void. Being inspired by frequent personal encounters with homeless persons and drawing on parallels between the effort of aesthetically appreciating mainstream artworks and the effort to cope with the negative aesthetic impressions generated by the homeless body, I argue that homelessness may not only be appreciated negatively but also may trigger lasting positive aesthetic experiences.